Age-Related Inflammatory Balance Shift, Nasal Barrier Function, and Cerebro-Morphological Status in Healthy and Diseased Rodents - Varga-Medveczky, Zsófia; Kovács, Noémi; Tóth, Melinda E.; Sántha, Miklós; Horváth, Ildikó; Bors, Luca Anna; Fónagy, Katalin; Imre, Timea; Szabó, Pál; Máthé, Domokos; Erdő, Franciska (Frontiers in Neuroscience, 2021)
Increased blood-brain barrier permeability and extensive neuronal changes have been described earlier both in healthy and pathological aging like APOB-100 and APP-PSEN1 transgenic mouse models. APOB-100 hypertrigliceridemic model is a useful tool to study the link between cerebrovascular pathology and neurodegeneration, while APP-PSEN1 humanized mouse is a model of Alzheimer’s disease. The aim of the current study was to characterize the inflammatory changes in the brain with healthy aging and in neurodegeneration. Also the cerebro-morphological and cognitive alterations have been investigated. The nose-to-brain delivery of a P-glycoprotein substrate model drug (quinidine) was monitored in the disease models and compared to the age-matched controls. Our results revealed an inflammatory balance shift both in the healthy aged and neurodegenerative models. In normal aging monocyte chemottractant protein-1, stem cell factor and Rantes were highly upregulated indicating a stimulated leukocyte status. In APOB-100 mice VEGF, PDGF-BB and IL-17A were induced (vascular reaction), while in APP-PSEN1 mice resistin, IL-17A and GM-CSF were mostly upregulated. The nasal drug absorption was similar in brain and the blood indicating the molecular bypass of the blood-brain barrier. The learning and memory tests showed no difference in the cognitive performance of healthy aged and young animals. Based on these results it can be concluded that various markers of chronic inflammation are present in healthy aged and diseased animals. In APOB-100 mice also a cerebro-ventricular dilation can be observed. For development of proper anti-aging and neuroprotective compounds further studies focusing on the above inflammatory targets are suggested.